Analysis of the Effect of Ownership Structure and Debt Structure on Earnings Management with Financial Distress as a Mediating Variable on the Indonesian Stock Exchange - jocelyn 1942018 (Universitas Internasional Batam, 2024)
This research aims to analyze and determine the relationship between ownership structure (ownership concentration, managerial ownership, financial institution ownership, family ownership) and debt structure (long-term debt and short-term debt) on earnings management which is mediated by financial difficulties. This research uses a quantitative method where data is tabulated from the annual financial reports of non-financial companies listed on the Indonesia Stock Exchange (BEI), obtained from 392 non-financial companies according to sample criteria from 2016-2020. The sample data that is the object of research is 1823 data. This research processes data using SmartPLS software to analyze panel regression so that conclusions can be drawn. The results of this study show that the variables ownership concentration, managerial ownership, non-financial institution ownership, family ownership, short-term debt and financial difficulties are not significant in influencing earnings management, but the variables financial institution ownership and long-term debt significantly influence earnings management. And managerial ownership is not significant in influencing financial difficulties. The financial difficulty variable as a mediating variable between shares owned by managers and earnings management does not have a significant mediating impact